Close-to-Nature Forestry Measures in East Polissia Region of Ukraine - Anatoly Mykolayovych Zhezhkun; Serhiy Kubrakov; Ihor Porokhniach; Ihor Kovalenko; Tetiana Melnyk (South-East European Forestry, 2023)
The article discusses close-to-nature forestry measures for the natural regeneration of pure and mixed pine forests. It is shown that successful natural regeneration of high value tree species takes place after uniformly gradual logging and progressive strip felling as final cutting operations in pure pine forests in fresh or moist oak-pine forest stands on sandy soil, resulting in the development of natural young pine forests with mixed composition. The article analyzes the state of natural regeneration after the first cycle of transformation felling operations in pure even-aged pine stands aimed at converting them into mixed pine forests of natural origin. Systems of close-to-nature silvicultural measures for restoration, development, improvement and regen